Research Paper: Patterns of Drunk and Drugged Driving in Fatally Injured Drivers in Tehran, Iran - Ghadirzadeh, Mohammadreza; Forouzesh, Mehdi; Barzegar, Abdolrazagh; Mirtorabi, Seyed Davood; Hedayatshodeh, Mohammadjavad; Mohajerpour, Amir Mohammad; Fallah, Fardin (International Journal of Medical Toxicology and Forensic Medicine, 2019)
Background: Substance abuse in drivers is a global public health concern. We investigated patterns of alcohol and illicit drug consumption in drivers died in traffic accidents in Tehran Province, Iran. Methods: In this cross-sectional study, presence of alcohol and illicit drugs in the body of dead drivers referred to Tehran Legal Medicine Organization during April 2016 to April 2018 were investigated. All participants underwent autopsy and their urine, visceral and vitreous samples were examined for alcohol and illicit drugs. Victims with Complete Toxicology Tests for both alcohol and non-alcoholic drugs and those autopsied during their first 24 hours of death were included. Victims’ demographic characteristics, results of their toxicology tests and accident-related factors were investigated, too. To warrant confidentiality of information, identities of victims were concealed. The obtained data were analyzed by SPSS V. 16 and statistically significant level was set at less than 0.05. Results: Of 618 study participants (mean age of 36.95 years), 601 (97.3%) were male. Of victims, 566 (91.3%) were city inhabitants and 471 (76.2%) were with educational attainment of lower than high school. The majority (93%) of crashes happened inside the city. Causes of death were head trauma in 519 (84%) cases, multiple traumas in 62 (10%) cases and bleeding in 37 (6%) cases. Multiple and single-vehicle accidents account for 498 (80.5%) and 98 (17.5%) crashes, respectively. A total of 73 (11.8%) cases were found positive for alcohol/drug consumption: 24 (4%) were alcohol positive, 52 (8.4%) were positive for non-alcoholic drugs (3 were positive for both). Main detected non-alcoholic drugs were morphine and tramadol. There was statistically significant association between drug/alcohol consumption of drivers and cause of death and crash mechanism (Both P<0.001). Multiple traumas and single vehicle crashes were more prevalent among drivers with drug/alcohol positive tests. Conclusion: Rate of alcohol use in our drivers was lower than many countries which is attributed to religious and legal issues. Consistent with the reported pattern of drug abuse in Iranian general population, opioids and tramadol were the main drugs of abuse among studied drivers. Drug or alcohol use result in drivers’ distraction and more fatal injuries.